Phylogenetic plant community structure along elevation is lineage specific. Issue 15 (8th November 2013) - Ndiribe, Charlotte; Pellissier, Loïc; Antonelli, Silvia; Dubuis, Anne; Pottier, Julien; Vittoz, Pascal; Guisan, Antoine; Salamin, Nicolas
Abstract: The trend of closely related taxa to retain similar environmental preferences mediated by inherited traits suggests that several patterns observed at the community scale originate from longer evolutionary processes. While the effects of phylogenetic relatedness have been previously studied within a single genus or family, lineage‐specific effects on the ecological processes governing community assembly have rarely been studied for entire communities or flora. Here, we measured how community phylogenetic structure varies across a wide elevation gradient for plant lineages represented by 35 families, using a co‐occurrence index and net relatedness index (NRI). We propose a framework that analyses each lineage separately and reveals the trend of ecological assembly at tree nodes. We found prevailing phylogenetic clustering for more ancient nodes and overdispersion in more recent tree nodes. Closely related species may thus rapidly evolve new environmental tolerances to radiate into distinct communities, while older lineages likely retain inherent environmental tolerances to occupy communities in similar environments, either through efficient dispersal mechanisms or the exclusion of older lineages with more divergent environmental tolerances. Our study illustrates the importance of disentangling the patterns of community assembly among lineages to better interpret the ecological role of traits. It also sheds light on studies reporting absence of phylogenetic signal, and opens new perspectives on the analysis of niche and trait conservatism across lineages. Abstract : Our study investigates the phylogenetic structure found in plant communities in a mountain study area. We show that the global patterns of community structure found do not correspond to those found in other studies, usually along smaller gradients and/or taxonomically more restricted. In particular, we demonstrate that large lineage‐specific differences exist, which highlight the need to reconsider global measures of phylogenetic community.